2016
DOI: 10.18869/acadpub.jafm.68.224.22690
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Effectiveness Enhancement Applying another Jet in the Upstream Neighbor of the Main Jet-Using LES Approach

Abstract: Flow hydrodynamic effects and film cooling effectiveness of placing a coolant port (upstream jet) just upstream of the main cooling jet were numerically investigated. The upstream jet was added such that the total cooling cross section (cross sections of the main and upstream jets) remains constant, in comparison to the case of ordinary cooling jet. The finite volume method and the unsteady SIMPLE algorithm on a multiblock non-uniform staggered grid arrangement were applied. The large eddy simulation (LES) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Kusterer et al (2007Kusterer et al ( , 2009 proposed the double-jet film cooling technology to establish an anti-kidney vortex, which would prevent the double jet from lifting off the surface and raise the lateral spreading of the cooling air. Salimi et al (2016) found that applying upstream jet film cooling configuration would have a significant improvement in the flow control capability and both centerline and span-wise averaged film cooling effectiveness. Sinha et al (1991) studied the film cooling effectiveness with variable density ratio, it could be concluded that decreases in density ratio and increases in momentum flux ratio were found to reduce the spreading of the film cooling jet and reduce laterally averaged effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Kusterer et al (2007Kusterer et al ( , 2009 proposed the double-jet film cooling technology to establish an anti-kidney vortex, which would prevent the double jet from lifting off the surface and raise the lateral spreading of the cooling air. Salimi et al (2016) found that applying upstream jet film cooling configuration would have a significant improvement in the flow control capability and both centerline and span-wise averaged film cooling effectiveness. Sinha et al (1991) studied the film cooling effectiveness with variable density ratio, it could be concluded that decreases in density ratio and increases in momentum flux ratio were found to reduce the spreading of the film cooling jet and reduce laterally averaged effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In the near past, Salimi et al [11] applied the upstream jet hole to enhance the film effectiveness of main hole through keeping the cross sections constant of the main and upstream jets compared with ordinary cooling jet. A novel sister shaped (SSH) and novel combined hole configuration were examined for the cooling performance over flat plate surface [12]- [13] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The film performance for six antivortex holes with different branch hole diameters and exit locations was further studied by Dhungel et al (2009) and Christopher et al (2013). Salimi et al (2016) studied the effects of adding another cooling port upstream of the main jet. A significant film cooling improvement was observed.…”
Section: Introductionmentioning
confidence: 99%